Hydropower Policy – A Critique - Shrestha, Ratna Sansar (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Not Available. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 20Page: 11-16